2017
DOI: 10.18632/oncotarget.14653
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor HBP1 is a direct anti-cancer target of transcription factor FOXO1 in invasive oral cancer

Abstract: Either FOXO1 or HBP1 transcription factor is a downstream effector of the PI3K/Akt pathway and associated with tumorigenesis. However, the relationship between FOXO1 and HBP1 in oral cancer remains unclear. Analysis of 30 oral tumor specimens revealed that mean mRNA levels of both FOXO1 and HBP1 in non-invasive and invasive oral tumors were found to be significantly lower than that of the control tissues, and the status of low FOXO1 and HBP1 (< 0.3 fold of the control) was associated with invasiveness of oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 36 publications
1
18
1
Order By: Relevance
“…We provide the first evidence showing that miR‐29a and miR‐92a promote the expansion of functional MDSCs via the Hbp1 /cell cycle pathway and the Prkar1a /PKA/p‐STAT3 pathway, respectively. HBP1 inhibits the G1 phase of the cell cycle and inhibits the proliferation of many types of tumor cells . However, few studies have investigated the relationship between MDSCs and cell cycle progression, and the effect of HBP1 on MDSCs has not been studied.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…We provide the first evidence showing that miR‐29a and miR‐92a promote the expansion of functional MDSCs via the Hbp1 /cell cycle pathway and the Prkar1a /PKA/p‐STAT3 pathway, respectively. HBP1 inhibits the G1 phase of the cell cycle and inhibits the proliferation of many types of tumor cells . However, few studies have investigated the relationship between MDSCs and cell cycle progression, and the effect of HBP1 on MDSCs has not been studied.…”
Section: Discussioncontrasting
confidence: 66%
“…HBP1 inhibits the G1 phase of the cell cycle and inhibits the proliferation of many types of tumor cells. 31,32 However, few studies have investigated the relationship between MDSCs and cell cycle progression, and the effect of HBP1 on MDSCs has not been studied. In our study, the miR-29a-mediated silencing of Hbp1 induced cell cycle progression in MDSCs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a previous study of Chan et al. investigated the influence of HBP1 on invasive oral cancer . Suppression of HBP1 could also promote human breast cancer cell migration and invasion .…”
Section: Discussionmentioning
confidence: 99%
“…HBP1, a tumor suppressor, has been shown to contribute to cell senescence and block tumorigenesis in several cancers [42], including lung adenocarcinoma (H1299 [p53−/−], A549), hepatocellular carcinoma (HepG2), and osteogenic sarcoma (U2OS). In addition, a previous study of Chan et al investigated the influence of HBP1 on invasive oral cancer [43]. Suppression of HBP1 could also promote human breast cancer cell migration and invasion [44].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of 30 noninvasive and invasive oral tumor specimens indicated that mean mRNA levels of both FOXO1 and HBP1 are significantly lower than those of control tissues, and a low FOXO1 and HBP1 status (<0.3‐fold of the control) is associated with enhanced invasiveness of oral tumors. Specifically, HBP1 knockdown potently downregulates FOXO1 and promotes the expression of malignant phenotypes, colony formation and invasion of oral cancer …”
Section: Roles Of Foxo1 In Diverse Human Neoplasmsmentioning
confidence: 99%